Evaluation of Pulmonary Infection in Rabbits by Tc-99m Hegzamethylene Propilene Amine Oxime Labeled Leukocyte Scintigraphy - Koc, Zehra Pinar; Bulut, Yasemin; Canpolat, Sinan; Uysal, Ayhan; Sarac, Andmehmet (Lippincott Williams & Wilkins, 2016)
Background/Purpose: The aim of this study was to determine the effectiveness of labeled leukocyte scintigraphy in pulmonary infection of rabbits and the effect of increasing the incubation duration in this efficiency. Materials and Methods: Five New Zealand white rabbits (5-6 months old, 2.5-3 kg) were the subjects of this study. The rabbits were divided into 3 groups (group1: control, group 2: tracheal inoculation group, and group 3: transthoracic inoculation group). The rabbits were inoculated by Escherichia coli administration 1 day before the scintigraphy in groups 2 and 3 rabbits. The labeled leucocytes scintigraphy was performed on all 5 rabbits. The images were evaluated by quantification (average counts in the lungs). The quantitative values were compared by paired samples t test, and a value of P < 0.05 was considered significant. Results: The labeling efficiency was similar in all 5 rabbits. The average counts in the lungs of group 2 were significantly higher than in groups 1 and 3. The second rabbit in group 3 (which had a prolonged waiting period in incubation with Tc-99m hexamethylpropyleneamine oxime) had average counts similar to group 1. Conclusions: The infection imaging by means of labeled leukocyte scintigraphy clearly demonstrates E. coli pneumonia in rabbits when they are inoculated by the transtracheal route. In addition, increasing the length of incubation with Tc-99m hexamethylpropyleneamine oxime with leukocyte does not have a benefit.
Keywords: pneumonia; infection imaging; experimental